The preparation of carbon-based materials from biomass by-product for application in adsorption and heterogeneous catalytic processes - Moulefera, Imane (UMA Editorial, 2021)
This PhD thesis is focused on the development of a methodology for the valorization of different types of lignins, Organosolv (Alcell) and Kraft, by the preparation of porous activated carbons with different textural and surface chemistry properties that allow a large adsorption capacity of emerging pollutants in aqueous phase and a high catalytic activity for alcohols decomposition reactions in gas phase.
Keywords: Catálisis - Tesis doctorales; Lignina - Tesis doctorales; Activated carbon; High surface area; Adsorption process; Catalytic process